Pressurised Intraperitoneal Aerosolised Chemotherapy-Results from the First Hundred Consecutive Procedures - Hoskovec, David; Krška, Zdeněk; Vočka, Michal; Argalácsová, Soňa; Dytrych, Petr (Cancers, 2024)
PIPAC is a new and promising technique for the intraperitoneal administration of chemotherapy. It can be used in patients with various peritoneal cancer metastases. It is mainly a palliative treatment, but there is some neoadjuvant treatment potential. We have operated on 41 patients with various intra-abdominal cancers. PIPAC was performed every 6 weeks. The indication was extension of peritoneal carcinomatosis beyond the criteria for cytoreductive surgery and HIPEC. The effect was evaluated according to the peritoneal cancer index, the peritoneal regression grading score and the amount of ascites. Complications were classified according to the Clavien-Dindo system. We have performed 100 PIPAC procedures. There were two major complications, classified as Clavien Dindo III (2%). The number of procedures varied from 1 to 6. Five patients switched to cytoreductive surgery and HIPEC, and one was indicated for the watch and wait strategy due to total regression according to PRGS. Three patients are still continuing treatment. The others stopped treatment mainly because of progression of the disease and loss of metastases. We observed a reduction in ascites production soon after PIPAC application. PIPAC is a safe and well-tolerated treatment modality. It is mainly a palliative treatment that can improve the quality of life by reducing the production of ascites, but in about 10% of cases, it can reduce the extent of the disease and allow for further radical treatment.
Keywords: peritoneal carcinomatosis; PIPAC; atomiser